1995
DOI: 10.1111/j.1432-1033.1995.tb20565.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Peroxisome Proliferators on Phosphoprotein Levels in Human and Rat Hepatic-Derived Cell Lines

Abstract: To elucidate the effect of peroxisome proliferators on the signal-transduction pathway, we have compared the effect of ciprofibrate, an hypolipaemic agent, on the overall phosphoprotein level between rat and human well differentiated hepatic derived cell lines. The phosphorylation status of several phosphoproteins in the rat Fao cell line was increased by the drug while no changes were observed in the human HepG2 cell line. In rat Fao cells, this increase, which is concentration and time dependent, can be as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Several years ago it was reported that P K C was stimulated in vitro by peroxisome proliferators [27]. We reported an increase in phosphorylation of several cellular phosphoproteins in the presence of ciprofibrate [28]. Recently, by using Fao-permeabilized cells, we reported that ciprofibrate in vivo stimulates the PKCdependent phosphorylation of a specific substrate [29].…”
Section: Protein Kinase C (Pkc) Mediates Peroxisome Proliferator Effectsmentioning
confidence: 87%
“…Several years ago it was reported that P K C was stimulated in vitro by peroxisome proliferators [27]. We reported an increase in phosphorylation of several cellular phosphoproteins in the presence of ciprofibrate [28]. Recently, by using Fao-permeabilized cells, we reported that ciprofibrate in vivo stimulates the PKCdependent phosphorylation of a specific substrate [29].…”
Section: Protein Kinase C (Pkc) Mediates Peroxisome Proliferator Effectsmentioning
confidence: 87%